1997
DOI: 10.1103/physreve.56.3540
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing time-resolved spectroscopic data from an azimuthally symmetric, aluminum-wire array,z-pinch implosion

Abstract: A 90-wire, aluminum, z-pinch experiment was conducted on the Saturn accelerator at the Sandia National Laboratories that exhibited azimuthally symmetric implosions and two x-ray bursts, a main burst and a subsidiary one. These bursts correlated with two consecutive radial implosions and are consistent with predicted magnetohydrodynamics behavior. A variety of time-resolved, accurately timed, spectroscopic measurements were made in this experiment and are described in this paper. These measurements include ͑1͒ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 18 publications
1
34
0
Order By: Relevance
“…These conditions are within the range of those attained in the Saturn Z pinches analyzed in Ref. [18]. Al ion temperatures ranging up to w30 keV were measured on Saturn Z-pinch experiments by Sanford et al [21].…”
Section: Description Of Benchmark and Calculation Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…These conditions are within the range of those attained in the Saturn Z pinches analyzed in Ref. [18]. Al ion temperatures ranging up to w30 keV were measured on Saturn Z-pinch experiments by Sanford et al [21].…”
Section: Description Of Benchmark and Calculation Methodsmentioning
confidence: 98%
“…The relevant literature is too extensive to fully cite here; for examples see Ref. [18], which analyzed 14 spectra from Al pinches on the Saturn generator at Sandia National Laboratories, and Ref. [19], which summarizes and extracts trends from Ar Z-pinch data collected since 1991 from 7 different drivers.…”
Section: Description Of Benchmark and Calculation Methodsmentioning
confidence: 99%
“…For K ≈ 1 (low n), the empirical factor 2 in reference [18] amends partially for the inaccuracy introduced there by the simplifying approximation of the uniformity of the NN-ion field. Taking E bind given by (2), and Z 0 = Z i , we find R crit.unif = 4n 2 a 0 /Z 0 , R crit.peak = 6n 2 a 0 /Z 0 . Thus, we find that the use of the factor of 1.5 3 = 3.375 restores the ideal-plasma NN-approximation result for hydrogen.…”
Section: Comparison With Results Found In Literaturementioning
confidence: 99%
“…Refs. [1][2][3][4][5][6][7][8]). However, the theoretical interpretation of experimental data, as well as the analysis of collisional-radiative kinetics in general, is still based on rather simplified treatments of plasma density effects.…”
Section: Introductionmentioning
confidence: 99%
“…Recent experiments have shown that compressional heating can be fairly non-uniform, leading to hot plasma cores and much cooler surrounding shells. [4][5][6] In strongly driven Z-pinch or inertial confinement fusion ͑ICF͒ plasmas, shock waves and/or sharp gradients in temperature and density can form. During the passage of a shock front, the plasma undergoes large, rapid, but predictable jumps in electron and ion temperature.…”
Section: Introductionmentioning
confidence: 99%